2013
DOI: 10.1039/c3mb25567k
|View full text |Cite
|
Sign up to set email alerts
|

Hh signaling inhibitors from Vitex negundo; naturally occurring inhibitors of the GLI1–DNA complex

Abstract: The hedgehog (Hh) signaling pathway has crucial roles in embryonic development, cell maintenance and proliferation, and is also known to contribute to cancer cell growth. New naturally occurring Hh inhibitors (1, 7 and 9) were isolated from Vitex negundo using our previously constructed cell-based assay. Bioactivity guided isolation provided 9 natural compounds including a new diterpene, nishindanol (9). Compounds 7 and 9 showed cytotoxicity against cancer cell lines in which Hh signaling was aberrantly activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…5) using the GLI1-DNA complex, as previously described. 19 Interestingly, despite the weak GLI1 transcriptional inhibition of compound 1, it showed potent inhibition of GLI1-DNA complex formation, whereas inactive 5 did not inhibit the complex Figure 1. Schematic of the constructed assay system.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…5) using the GLI1-DNA complex, as previously described. 19 Interestingly, despite the weak GLI1 transcriptional inhibition of compound 1, it showed potent inhibition of GLI1-DNA complex formation, whereas inactive 5 did not inhibit the complex Figure 1. Schematic of the constructed assay system.…”
Section: Resultsmentioning
confidence: 96%
“…1), allowing us to identify several potent Hh inhibitors such as physalin B, 14 physalin F, 14 colubrinic acid, 15 cardenolides, 16 taepeenin D, 17 flavonoid glycoside, 18 vitetrifolin D, 19 and physalin H. 20 During the present investigation, a screening study revealed that Artocarpus communis and Hyptis suaveolens exhibit inhibitory activity against the Hh signal. Here we report five new natural products (6, 7, and 9-11) as moderate Hh inhibitors and four as potent Hh inhibitors (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 77%
“…Using this assay system, we isolated a number of naturally occurring inhibitors of the Hh signaling pathway, for example, physalin B and physalin F [12], colubrinic acid [13], cardenolides [14], taepeenin D [15], a flavonoid glycoside [16], acoschimperoside P [17], and vitetrifolin D [18]. During the screening of the plant extract library with the assay system, we identified some plant extracts as GLI1-mediated transcriptional inhibitor samples.…”
Section: Introductionmentioning
confidence: 99%
“…2). Previously, we have reported several naturally occurring Hh inhibitors, such as physalin B, 14 physalin F, 14 colubrinic acid, 15 caldenolides, 16 taepeenin D, 17 flavonoid glycoside, 18 vitetrifolin D, 19 and physalin H, 20 using this bioactivity-guided isolation assay.…”
mentioning
confidence: 96%